Brucella induces an unfolded protein response via TcpB that supports intracellular replication in macrophages. - Judith A Smith; Mike Khan; Diogo D Magnani; Jerome S Harms; Marina Durward; Girish K Radhakrishnan; Yi-Ping Liu; Gary A Splitter (PLoS Pathogens)
Brucella melitensis is a facultative intracellular bacterium that causes brucellosis, the most prevalent zoonosis worldwide. The Brucella intracellular replicative niche in macrophages and dendritic cells thwarts immune surveillance and complicates both therapy and vaccine development. Currently, host-pathogen interactions supporting Brucella replication are poorly understood. Brucella fuses with the endoplasmic reticulum (ER) to replicate, resulting in dramatic restructuring of the ER. This ER disruption raises the possibility that Brucella provokes an ER stress response called the Unfolded Protein Response (UPR). In this study, B. melitensis infection up regulated expression of the UPR target genes BiP, CHOP, and ERdj4, and induced XBP1 mRNA splicing in murine macrophages. These data implicate activation of all 3 major signaling pathways of the UPR. Consistent with previous reports, XBP1 mRNA splicing was largely MyD88-dependent. However, up regulation of CHOP, and ERdj4 was completely MyD88 independent. Heat killed Brucella stimulated significantly less BiP, CHOP, and ERdj4 expression, but induced XBP1 splicing. Although a Brucella VirB mutant showed relatively intact UPR induction, a TcpB mutant had significantly compromised BiP, CHOP and ERdj4 expression. Purified TcpB, a protein recently identified to modulate microtubules in a manner similar to paclitaxel, also induced UPR target gene expression and resulted in dramatic restructuring of the ER. In contrast, infection with the TcpB mutant resulted in much less ER structural disruption. Finally, tauroursodeoxycholic acid, a pharmacologic chaperone that ameliorates the UPR, significantly impaired Brucella replication in macrophages. Together, these results suggest Brucella induces a UPR, via TcpB and potentially other factors, that enables its intracellular replication. Thus, the UPR may provide a novel therapeutic target for the treatment of brucellosis. These results also have implications for other intracellular bacteria that rely on host physiologic stress responses for replication.